2022
DOI: 10.1021/acs.orglett.2c02370
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Electro-Oxidative C–C and C–N Coupling and Aromatization for the Construction of Pyrazine-Fused Bis-aza[7]helicene

Abstract: Repeated tandem electro-oxidative C−C and C−N coupling and aromatization were employed for the efficient construction of aza[7]helicene (BA7) as a key intermediate and the targeted pyrazine-fused bis-aza[7]helicene (PBBA7) derivatives in 90.0−93.2% isolated yields under a controlled potential. The electrosynthetic protocol showed high selectivity and enabled rapid access to functionalized organic conjugated materials from readily available polycyclic aromatic amines. A synthetic mechanistic study along with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In electrochemical syntheses, no oxidant is required, and oxidative transformations can be conducted under mild reaction conditions [7] . Electrosynthetic approaches of helicenes were quite rare [8a] until 2022, when Lei, Yu, and co‐workers reported a tandem electro‐oxidative protocol for the construction of pyrazine‐fused bis‐aza[7]helicene from 6‐aminochrysene in high yields [8b] . Although, the electrochemical oxidative coupling of arenols has been established, to our knowledge, no one has applied this success to get helicenes directly from arenols via a sequential electrochemical protocol [9] .…”
Section: Figurementioning
confidence: 99%
“…In electrochemical syntheses, no oxidant is required, and oxidative transformations can be conducted under mild reaction conditions [7] . Electrosynthetic approaches of helicenes were quite rare [8a] until 2022, when Lei, Yu, and co‐workers reported a tandem electro‐oxidative protocol for the construction of pyrazine‐fused bis‐aza[7]helicene from 6‐aminochrysene in high yields [8b] . Although, the electrochemical oxidative coupling of arenols has been established, to our knowledge, no one has applied this success to get helicenes directly from arenols via a sequential electrochemical protocol [9] .…”
Section: Figurementioning
confidence: 99%
“…A series of pyrazine-fused bis-aza[7]helicene (PBBA7) derivatives, synthesized by repeated tandem electro-oxidative C−C and C−N coupling and aromatization in 90.0–93.2% isolated yields, were reported by Yu et al [ 32 ]. The PBBA7-C16 was utilized as the HTM for perovskite solar cells.…”
Section: Azahelicenes In Pscsmentioning
confidence: 99%
“…Thus, it is desirable to develop alternative HTMs with low cost of production and appropriate properties capable of significantly improving the efficiency and stability of devices. Different molecular frameworks with spiro-type core [ 17 , 18 , 19 , 20 , 21 ], D-π-D [ 22 , 23 , 24 , 25 ], D-A-D [ 26 , 27 ], and helicenes [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] have been explored to evaluate their applicability as HTMs for n-i-p PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, compounds 2a-p were treated with hydrazine hydrate in an undivided cell equipped with graphite carbon (2 cm 2 ) both as an anode and a cathode at room temperature (25 °C), and a constant voltage of −0.2 V was applied under ambient atmosphere for 30 min. It was found that the desired products 3a-p were formed in good to excellent yields of 75-94% in the presence of ethanol as a solvent and NaClO 4 as an electrolyte [21][22][23] as shown in Scheme 2. The data for electro-organic synthesis of hydrazone derivatives (3a-p) along with used potentials are shown in Table 2.…”
Section: Communicationmentioning
confidence: 99%